Legality of Electronic Wills (Comparative Study Between Indonesian Conventional Wills And Electronic Wills in the State Of Indiana) - Ahmad Jayadi; Salim HS; Aris Munandar (MultiTech Publisher, 2024)
This thesis examines the legality of electronic wills with a focus on a comparison between conventional wills in Indonesia and electronic wills in the state of Indiana, United States. The background to this study is based on the rapid development of technology, which has changed the paradigm of human communication and has had a significant impact on various aspects of life, including inheritance law. Digital technology has introduced new forms of legal instruments, such as electronic wills, which offer efficiency and convenience in the creation and management of legal documents. This research uses a comparative descriptive method to analyze the legality of conventional wills in Indonesia, the legality of electronic wills in Indiana, and compares these two systems to understand the similarities and differences as well as their legal implications. The data used is secondary data obtained from documentation, literature, legal regulations and related documents. The research results show that although electronic wills offer convenience and efficiency, there are significant challenges regarding security, trust and legal legitimacy. It is hoped that this research can contribute to legal literature and academic needs and become a basis for policy makers in developing regulations that support the application of technology in the inheritance law system.